Effect of the Interaction between Recanalization and Collateral Circulation on Functional Outcome in Acute Ischaemic Stroke. Issue 6 (November 2014) - Mangiafico, Salvatore; Saia, Valentina; Nencini, Patrizia; Romani, Ilaria; Palumbo, Vanessa; Pracucci, Giovanni; Consoli, Arturo; Rosi, Andrea; Renieri, Leonardo; Nappini, Sergio; Limbucci, Nicola; Inzitari, Domenico; et al.
Identification of patients with acute ischaemic stroke who could most benefit from arterial recanalization after endovascular treatment remains an unsettled issue. Although several classifications of collateral circulation have been proposed, the clinical role of collaterals is still debated. We evaluated the effect of the collateral circulation in relation to recanalization as a predictor of clinical outcome. Data were prospectively collected from 103 patients consecutively treated for proximal middle cerebral or internal carotid artery occlusion. The collateral circulation was evaluated with a novel semiquantitative-qualitative score, the Careggi collateral score (CCS), in six grades. Both CCS and recanalization grades (TICI) were analysed in relation to clinical outcome. A statistical analysis was performed to evaluate the effect of interaction between recanalization and collateral circulation on clinical outcome. Out of the 103 patients, 37 (36.3%) had poor collaterals, and 65 (63.7%) had good collaterals. Patients with good collaterals had lower basal National Institute of Health Stroke Scale (NIHSS), more distal occlusion, smaller lesions at 24h CT scan and better functional outcome. After multivariate analysis, the interaction between recanalization and collateral grades was significantly stronger as a predictor of good outcome (OR 6.87, 95% CI 2.11–22.31) or death (OR 4.66, 95% CI 1.48–14.73) compared to the effect of the single variables. Collaterals showed an effect of interaction with the recanalization grade in determining a favourable clinical outcome. Assessment of the collateral circulation might help predict clinical results after recanalization in patients undergoing endovascular treatment for acute ischaemic stroke.